Islam, Marriage Law and the Legal Framework of England and Wales - Garcia Oliva, Javier; Hall, Helen (Revista de Estudios Jurídicos y Criminológicos, 2022)
This article examines Islam and in Contemporary England and Wales, and asks what issues faced by Muslims may reveal about the legal landscape more widely, using marriage law as a case study. It opens with an overview of Religion, Islam and the Legal Framework in England and Wales, before addressing the modern Law on the solemnisation of marriages and current proposals for reform. It then moves to examine the conscious choice of some Muslims to enter into purely religious marriages, and asks what this reveals about Muslim communities and the overarching legal framework. In the concluding section, the piece then addresses what can be learnt about two observable realities from marriage law: 1) the Continued Problematisation of Muslims and Muslim Communities in popular and academic perception, and 2) the significance of unregistered religious marriages for other voluntary adult partnerships outside of the system of state registration.